Вплив програмованої сенсорної депривації на стан нейропсихологічних показників у хворих з сіалоаденітом = The effect of the programmed sensory deprivation on state of neuropsychological performance in patients with sialoadenitom - Кrinichkо V. V. (Journal of Education, Health and Sport, 2016)
Кrinichkо V. V. Вплив програмованої сенсорної депривації на стан нейропсихологічних показників у хворих з сіалоаденітом = The effect of the programmed sensory deprivation on state of neuropsychological performance in patients with sialoadenitom Journal of Education, Health and Sport. 2016;6(10):510-519. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.167119 http://ojs.ukw.edu.pl/index.php/johs/article/view/4001 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. Вплив програмованої сенсорної депривації на стан нейропсихологічних показників у хворих з сіалоаденітом В. В. Криничко Медичний центр "Інтермед", м. Харків Реферат Автор, грунтуючись на результатах лікування 97 хворих з сіалоаденітом, що були проліковані методом програмованої сенсорної депривації, встановив, що даний метод лікування значно покращує психологічний стан обстежених, суб’єктивне відчуття пацієнтів, зменшував депресивні та тривожні розлади, агресію. Ключові слова: програмована сенсорна депривація, нейропсихологічне дослідження, сіалоаденіти. The effect of the programmed sensory deprivation on state of neuropsychological performance in patients with sialoadenitom V. V. Кrinichkо Medical Center "Іntеrmеd", Kharkov Abstract The author based on the results of treatment of 97 patients with sialoadenitom who were treated using the method programmed sensory deprivation, found that this treatment significantly improves the psychological state of the patients, subjective feelings of patients, reduces depression and anxiety disorders, aggression. Keywords: programmed sensory deprivation, neuropsychological study sialoadenity.